Automaticity of lexical access and executive control in Croatian-German bilinguals and second language learners - Vujnović Malivuk, Kristina; Palmović, Marijan; Zergollern-Miletić, Lovorka (Studies in Second Language Learning and Teaching, 2018)
The aim of this study was to explore automaticity of lexical access and executive functions of language learners and bilinguals while considering their language automaticity. Three groups of youths aged 14 to 18 were tested: Croatian-German early bilinguals, Croatian high school students who participated in a German immersion programme at school and Croatian high school students of German as a foreign language. The participants were tested on a modified version of the Stroop test (i.e., a Stroop-like test). It presented pictures of an animal or an object with names of an animal or an object written over the picture. The names were written in Croatian or German and were either congruent or incongruent. Lexical access was slower for the bilinguals in both Croatian and German, which suggests that they used more of their cognitive resources because both of their languages were highly active, and more executive control was required to complete the task.